LDL Subtypes and Its Association With Stroke A Case-Control Study - Shumi, Shamima Islam; Hoque, Mozammel; Ahmed, Afsana; Moutushi, Shafia Sharmin; Saha, Shantona; Islam, Tanzida; Aziz, Masood Md Abdul (Journal of Dhaka National Medical College & Hospital, 2016)
Cardiovascular disease (CVD) or stroke is one of the most common cause of mortality and long term severe disability. Hyper cholesterolemia facilitate atherosclerosis of cerebral arteries leading to ischaemic stroke. Atherosclerotic vascular disease is directly related to plasma cholesterol level. Traditionally estimation of total serum cholesterol and LDL-c are used as an indicator of atherogenicity. But subject may develop stroke with normal level of LDL cholesterol. So assessment of LDL-cholesterol concentration may not entirely reflect its atherogenic potential. Because LDL-c is not a single entity rather it consist of seven distinct subclasses of different particle size. The size of LDL particle is inversely correlated to their atherogenecity. Smaller LDL particles are consider to have more atherogenic profile than those with larger particles despite of identical total cholesterol levels. Therefore individual having smaller LDL particles are more atherogenic and more at risk to develop stroke even with normal LDL cholesterol concentration. So measurement of small dense LDL particle is more important than any other lipid measure. With this aim 91 stroke patients were selected as case and 40 were healthy control. The mean age of cases and controls were 49.60 ±12.88 years, 40.28 ±11.88 years respectively. Serum apo-B was measured in all study subject. The amount of apo-B is almost similar in every LDL subtype but the amount of cholesterol increases with the increasing particle size. So the ratio of cholesterol to apo-B decreases as the particles size decreases, thus LDL cholesterol /apo-B < 1 indicate the presence of atherogenic small dense LDL. So the prevalence of small dense LDL was evaluated by calculating the ratio of LDL-C/apo-B. The ratio was significantly lower in normolipidaemic stroke cases (0.73+0.23) compared to controls as well as dyslipidaemic stroke cases, indicating the presence of sd LDL in normolipidaemic stroke case. So it can be concluded that sd LDL is isolatedly associated with stroke in normolipidaemic individuals and it is independent of conventional lipid measure J. Dhaka National Med. Coll. Hos. 2016; 22 (02): 17-20